2010
DOI: 10.1093/ilar.51.2.149
|View full text |Cite
|
Sign up to set email alerts
|

Verification of Poultry Carcass Composting Research through Application during Actual Avian Influenza Outbreaks

Abstract: An avian influenza outbreak in 2002 affected 197 poultry farms in Virginia and cost an estimated $130 million in losses and cleanup. In 2004-2005, researchers initiated a project to investigate the feasibility and practicality of in-house composting of turkey mortalities (heavy hens and toms) as a method of disposal and disease containment. Occurrences of low pathogenic avian influenza (LPAI) in West Virginia and Virginia in 2007 provided an opportunity for first responders to verify composting as an effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…Although foam can take longer for ducks to reach unconsciousness than CO 2 gas on an individual basis, when set-up before depopulation and clean-up after depopulation of an entire flock are taken into consideration, foam offers additional savings in time and labor . Foam also has potentially better biosecurity because the birds do not leave the house, fewer people are needed to enter the house, and in-house composting is compatible with foam depopulation, which means that infected waste does not have to leave the building (Benson et al, 2008;Flory and Peer, 2010). Water-based foam results in longer times to unconsciousness and death than CO 2 gassing approaches when tested on individual ducks.…”
Section: Figure 5�mentioning
confidence: 99%
See 1 more Smart Citation
“…Although foam can take longer for ducks to reach unconsciousness than CO 2 gas on an individual basis, when set-up before depopulation and clean-up after depopulation of an entire flock are taken into consideration, foam offers additional savings in time and labor . Foam also has potentially better biosecurity because the birds do not leave the house, fewer people are needed to enter the house, and in-house composting is compatible with foam depopulation, which means that infected waste does not have to leave the building (Benson et al, 2008;Flory and Peer, 2010). Water-based foam results in longer times to unconsciousness and death than CO 2 gassing approaches when tested on individual ducks.…”
Section: Figure 5�mentioning
confidence: 99%
“…Carbon dioxide gas causes hypercapnic hypoxia, by displacing the oxygen in the air surrounding the bird as well as decreasing the pH of the blood (Gerritzen et al, 2006b). Water-based foam was used to depopulate approximately 50,000 turkeys positive for LPAIV in 2 separate incidents in 2007 (Flory and Peer, 2010). A previous study by Benson et al (2009) showed that foam can be successfully used to depopulate ducks; however, the time it took for the animals to reach unconsciousness and brain death was not recorded and only a limited number of birds were used in the study.…”
Section: Introductionmentioning
confidence: 99%
“…Composting has been shown to be an effective means for virus neutralization in AI outbreaks and is now considered one of the preferred methods in the US [15][16][17]. According to a study in 2003, the AI virus in manure is neutralized within 15 min at 56°C (133°F), 24 h at 30-37°C (86-99°F) and 2 days at ambient temperatures of 15-20°C (59-68°F) [18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in a study by Glanville et al [22], biosecurity was demonstrated to be highly effective when the compost piles were capped with sufficient non-infected carbon material. Due to its low transportation costs and the creation of a usable, marketable end-product as a soil amendment, composting is the most cost-effective means of disposal as well as the most environmentally sound and biosecure and carries a positive public perception [15,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation